Juvenile handling rescues autism-related effects of prenatal exposure to valproic acid - Seiffe, Araceli (2022)
Environmental factors acting on young animals affect neurodevelopmental trajectories and impact adult brain function and behavior. Psychiatric disorders may be caused or worsen by environmental factors, but early interventions can improve performance. Understanding the possible mechanisms acting upon the developing brain could help identify etiological factors of psychiatric disorders and enable advancement of effective therapies. Research has focused on the long-lasting effects of environmental factors acting during the perinatal period, therefore little is known about the impact of these factors at later ages when neurodevelopmental pathologies such as autism spectrum disorder (ASD) are usually diagnosed. Here we show that handling mice during the juvenile period can rescue a range of behavioral and cellular effects of prenatal valproic acid (VPA) exposure. VPA-exposed animals show reduced sociability and increased repetitive behaviors, along with other autism-related endophenotypes such as increased immobility in the forced swim test and increased neuronal activity in the piriform cortex (Pir). Our results demonstrate that briefly handling mice every other day between postnatal days 22 and 34 can largely rescue these phenotypes. This effect can also be observed when animals are analyzed across tests using an “autism” factor, which also discriminates between animals with high and low Pir neuron activity. Thus, we identified a juvenile developmental window when environmental factors can determine adult autism-related behavior. In addition, our results have broader implications on behavioral neuroscience, as they highlight the importance of adequate experimental design and control of behavioral experiments involving treating or testing young animals.